2006
DOI: 10.1007/s11664-006-0282-y
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Si (211) surface

Abstract: Silicon (211) has been proposed as an alternative substrate for CdTe/HgCdTe molecular beam epitaxial growth. Silicon has a clear advantage over other substrates because of its low cost, high strength, and thermal-expansion coefficient, which matches that of the silicon readout integrated circuit. The (211) orientation has been shown to yield high-quality CdTe and HgCdTe/CdTe layers over other orientations. The reconstruction and faceting of the Si (211) surface is poorly understood despite the importance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A wide range of surfaces in vacuum are known to reconstruct, i.e., spontaneously rearrange the atom structure to lower the surface energy, 518 and thus it is natural to expect that NWs made out of the same material will also undergo reconstructions. The reconstruction can even determine the shape of the wire, for instance, the ͕112͖ surface of Si can reconstruct to a relatively low energy configuration 519,520 ͑see Fig. 78͒.…”
Section: Effects Of Irradiation On Nanowiresmentioning
confidence: 99%
“…A wide range of surfaces in vacuum are known to reconstruct, i.e., spontaneously rearrange the atom structure to lower the surface energy, 518 and thus it is natural to expect that NWs made out of the same material will also undergo reconstructions. The reconstruction can even determine the shape of the wire, for instance, the ͕112͖ surface of Si can reconstruct to a relatively low energy configuration 519,520 ͑see Fig. 78͒.…”
Section: Effects Of Irradiation On Nanowiresmentioning
confidence: 99%
“…Only recently, the attention has been drawn to higher index Si substrates, e.g., ͑211͒ and ͑311͒. 7 The combination of Si͑111͒ and Si͑001͒ surface bonding configurations in many high index substrates of ͑h11͒ type 8 can be useful for III-V materials growth as GaP and GaN. 9,10 On Si͑311͒ Tanikawa et al 11 have demonstrated the growth of polarization reduced GaN layers by structuring the substrates to form inclined Si͑111͒ planes on which c-axis oriented GaN is grown selectively.…”
mentioning
confidence: 99%
“…The third publication [10] involved an attempt to provide a more detailed analysis of the complex LEED pattern of the clean Si(211) surface. Although a structural model of clean Si(211) involving nanofacets was proposed by Baski, et al [6] on the basis of STM images, no attempt had previously been made to rationalize the LEED pattern in terms of the nanofaceted structural model.…”
Section: Resultsmentioning
confidence: 99%